Constraints on leisure time physical activity at a public university - Öcal, Kubilay (Journal of Human Sciences, 2014)
This study focuses on understanding constraints on leisure time physical activity (LTPA) on a university campus. The survey study was conducted with public university students (n=563) living in dormitories. The 38-item, 8-dimension Leisure Time Physical Activity Constraints (LTPA-C) Scale was used to investigate factors limiting LTPA. Age, gender, working status (i.e. part-time, non-working), program type (i.e. morning education, evening education), relationship status (i.e. in a relationship, not in a relationship), monthly expenses and body mass index (BMI) category (i.e. underweight, normal weight, overweight, obese) are key variables believed to affect LTPA-C. An initial confirmatory factor analysis was conducted to validate the structure of the scale, and frequency analysis, Pearson’s Correlation and t-tests were conducted to analyze the survey responses. Results showed the hierarchy of constraints for males (from high to low) to be as follows: society, income, time, facility, willpower, skill perception, family, body perception. The hierarchy was nearly identical for females, except ‘willpower’ was found to be a greater constraint than ‘facility’; moreover, the differences in the rates at which males and females perceived ‘facility’ and ‘willpower’ to be constraints were statistically significant. The study findings indicate that by taking steps to improve the infrastructure of university campus facilities and organize group activities, university management can provide motivation and social support that can help to increase university student participation in LTPA.